The Induction vacuum smelting of Co-Al-W superalloys – optimizing the feedstock based on the alloy’s chemical composition, elemental segregation, and slag formation - Mikuszewski, Tomasz; Tomaszewska, Agnieszka; Moskal, Grzegorz; Migas, Damian; Witala, Bartosz (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
In this study, the manufacturing of Co-Al-W alloys by smelting in a vacuum induction furnace was discussed taking into account the optimizing of the feedstock material morphology. Herein, the influence of various feedstock conditions and the order of introducing the alloying elements into a liquid alloy were analyzed and described. The investigation revealed that it was possible to obtain the desired chemical composition of Co-Al-W alloys using fragmented tungsten pellets introduced from a vacuum feeder into the liquid Co-Al alloy heated above the liquidus temperature to maximum of 40-50 °C. This technical variant required accurate temperature control of the molten alloy, which did not ensure complete reproducibility. The disadvantage of this process was a relatively high slag formation. The optimal technical solution involved obtaining the liquid Co-W solution and introducing Al at the end of the smelting process; in this variant, the slagging effect was relatively low. Additionally, melting of the alloy in an argon atmosphere reduced the loss of aluminum due to evaporation, as compared to melting in a vacuum. The smelting process could be carried out either in Al2O3 solid crucibles or in compacted crucibles made of MgO-based refractory mass.